Study On Emulsion Stability And Chemical Demulsification Characteristics Of Crude Oil Emulsion - Bambang, Pramudono (2005)

(untitled)
The formation of water-in-crude oil emulsion creates many problems in petroleum industry such as decreasing the oil recovery efficiency, high pumping cost, and piping corrosion, which needs to be treated. This formation of emulsion has been identified to be stabilised by natural surfactants consisted of carboxylic acids, phenols, asphaltenes, resins, and waxes. Several techniques have been used to destabilise the emulsion such as by using demulsifiers. However, so far, the selection of a demulsifier has been based on the trial and error method, which is very tedious. In order to develop the demulsifier selection method, a comprehensive knowledge of crude oil emulsion stability and how the demulsifier destabilises the crude oil emulsion is crucial, which needs to be studied. Therefore, this study is aimed to address this fundamental aspect by analysing the stability of six different crude oil samples, carrying out chemical demulsification study to develop a method for characterising and selecting the demulsifiers systematically, and determining the rate and mechanism of demulsification process. The stability study was carried out by analysing the water concentration and hold-up profiles, and the sedimentingcoalescing interface behaviour. It was found that there exists a correlation between the chemical properties of the crude oil such as resin-asphaltene ratio, asphaltene and solid contents, with emulsion formation and stability. A chemical demulsification experiment of crude oil emulsion was carried out using a wide range of demulsifiers used as a single demulsifiers. The demulsifier characteristics and demulsifier performance indicators were used as indicators for demulsifier selection. The results show that several indicators such as functional group, HLB number, demulsifier solubility, demulsifier effectiveness, partition coefficient, interfacial pressure, and interfacial activity have a significant correlation to the percentage of water and oil separations, which can be used to develop a method for screening the demulsifiers. By developing a mathematical model, both flocculation and coalescence rate constants, and the rate constant ratios (ano/K) can be predicted to determine the mechanism of emulsion breaking. It was found that higher (>7) and lower (<1) of the rate constant ratios demonstrate that the rate controlling step is determined by the coalescence and flocculation process respectively. While the rate constant ratios between 1 and 7 the rate controlling step is determined by both processes. The model validation by experimental data for various systems shows that the proposed model is applicable for both crude and synthetic oil emulsions. In order to obtain deeper understanding several recommendations such the effect of high pressure and temperature on emulsion formation and stability, the effect of composite demulsifiers on demulsification performance, and the thermodynamic modeling of chemical demulsification process are suggested for further studies.